2013
DOI: 10.1093/trstmh/trt016
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium vivax malaria in Duffy-negative individuals from Ethiopia

Abstract: The Duffy antigen (Fy) is necessary for Plasmodium vivax invasion of human erythrocytes. Some populations have a highly prevalent Fy-negative phenotype; such persons are naturally protected from P. vivax blood infection but are expected to completely support the P. vivax pre-erythrocytic cycle, representing a valuable model for studying the immune response during these parasitic stages. We typed 214 individuals, mostly Afro-Colombians, from a P. vivax-endemic area for Fy expression and determined the antibody … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 15 publications
5
62
2
1
Order By: Relevance
“…Since ape P. vivax is highly prevalent, especially in west central Africa, wild-living chimpanzees and gorillas could serve as an infection reservoir, especially in areas where an influx of Duffy positive humans through commerce and travel coincides with increasing forest encroachment and ape habitat destruction. Although Duffy negative individuals are generally protected from blood stage infections, recent studies in Madagascar 39 and Ethiopia 40 have shown that P. vivax is not absolutely dependent on the Duffy receptor. It will thus be important to assess the potential of ape parasites to acquire this phenotype, once the underlying genetic determinants have been identified in human strains.…”
Section: Discussionmentioning
confidence: 98%
“…Since ape P. vivax is highly prevalent, especially in west central Africa, wild-living chimpanzees and gorillas could serve as an infection reservoir, especially in areas where an influx of Duffy positive humans through commerce and travel coincides with increasing forest encroachment and ape habitat destruction. Although Duffy negative individuals are generally protected from blood stage infections, recent studies in Madagascar 39 and Ethiopia 40 have shown that P. vivax is not absolutely dependent on the Duffy receptor. It will thus be important to assess the potential of ape parasites to acquire this phenotype, once the underlying genetic determinants have been identified in human strains.…”
Section: Discussionmentioning
confidence: 98%
“…There have been other reports of P. vivax elsewhere on the African continent where P. vivax was initially thought to be non-existent or that the population was refractory to infection. These countries include Angola [6], Equatorial Guinea [6,7], Madagascar [8], Mauritania [9], Sudan [10], Kenya [11], Sao Tomé and Principe [12-15], Congo [14], Mali [16], and Ethiopia [17]. Although the exact prevalence data for P. vivax in Africa is not known, the parasites seem to be more prevalent in countries where many Duffy positive people are permanent residents [8,9,11].…”
Section: Discussionmentioning
confidence: 99%
“…Although epidemiologic histories could suggest the species (e.g., P. ovale is much more likely than P. vivax in a patient from West Africa) (21), clinical and reference laboratories rarely are provided such important information about pretest probability. Furthermore, epidemiologic histories also may be misleading, since recent work has shown that P. vivax merozoites do not absolutely require Duffy surface antigens to invade erythrocytes (22) and clinical P. vivax malaria can occur in some Duffy-negative individuals (23). These findings highlight the importance of developing and applying species-specific molecular assays to support rigorous scientific enquiry in addition to clinical care.…”
Section: Figmentioning
confidence: 99%